Monoclonal antibodies targeting the disintegrin-like domain of ADAMDEC1 modulates the proteolytic activity and enables quantification of ADAMDEC1 protein in human plasma. Issue 1 (2nd January 2018) - Lund, Jacob; Elimar Bitsch, Anne Mette; Grønbech Rasch, Morten; Enoksson, Mari; Troeberg, Linda; Nagase, Hideaki; Loftager, Mette; Overgaard, Michael Toft; Petersen, Helle Heibroch
ABSTRACT: Decysin-1 (ADAMDEC1) is an orphan ADAM-like metalloprotease with unknown biological function and a short domain structure. ADAMDEC1 mRNA has previously been demonstrated primarily in macrophages and mature dendritic cells. Here, we generated monoclonal antibodies (mAbs) against the mature ADAMDEC1 protein, as well as mAbs specific for the ADAMDEC1 pro-form, enabling further investigations of the metalloprotease. The generated mAbs bind ADAMDEC1 with varying affinity and represent at least six different epitope bins. Binding of mAbs to one epitope bin in the C-terminal disintegrin-like domain efficiently reduces the proteolytic activity of ADAMDEC1. A unique mAb, also recognizing the disintegrin-like domain, stimulates the caseinolytic activity of ADAMDEC1 while having no significant effect on the proteolysis of carboxymethylated transferrin. Using two different mAbs binding the disintegrin-like domain, we developed a robust, quantitative sandwich ELISA and demonstrate secretion of mature ADAMDEC1 protein by primary human macrophages. Surprisingly, we also found ADAMDEC1 present in human plasma with an approximate concentration of 0.5 nM. The presence of ADAMDEC1 both in human plasma and in macrophage cell culture supernatant were biochemically validated using immunoprecipitation and Western blot analysis demonstrating that ADAMDEC1 is secreted in a mature form.